2015
DOI: 10.4269/ajtmh.15-0170
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Encephalitis: The First Human Case Recorded in Brazil

Abstract: Abstract. A Brazilian ranch worker with encephalitis and flaccid paralysis was evaluated in the regional Acute

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 11 publications
3
40
0
7
Order By: Relevance
“…mosquitoes also demonstrate ornithophilic behavior. Just recently, antibodies against West Nile virus (WNV) were detected in equines and in chickens in Brazil [51], with the first detection of this virus in humans occurring in 2014 [52]. Other human encephalitis viruses that have birds as reservoirs are transmitted in Brazil, such as the Rocio virus [53], the Mayaro virus [54], the Venezuelan equine encephalitis virus (VEEV) [17] and the Saint Louis encephalitis virus [53].…”
Section: Discussionmentioning
confidence: 99%
“…mosquitoes also demonstrate ornithophilic behavior. Just recently, antibodies against West Nile virus (WNV) were detected in equines and in chickens in Brazil [51], with the first detection of this virus in humans occurring in 2014 [52]. Other human encephalitis viruses that have birds as reservoirs are transmitted in Brazil, such as the Rocio virus [53], the Mayaro virus [54], the Venezuelan equine encephalitis virus (VEEV) [17] and the Saint Louis encephalitis virus [53].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with conventional RT-PCR, real-time RT-PCR has several advantages such as rapidity, low risk of false positive results, high sensitivity, specificity, and the possibility of viral quantification (12) (19) (20) . In fact, a previously described real-time RT-PCR method (11) was able to detect a broad range of flaviviruses found in Brazil (3) (21) (22) . This assay amplified the genomes of 12 mosquito-borne flavivirusesthat are among the principal arboviruses responsible for human disease in Brazil (Table 2) (3) (23) .…”
Section: Discussionmentioning
confidence: 99%
“…Using serological methods, several studies identified as major infectious agents involved in GBS: Campylobacter jejuni , Mycoplasma pneumoniae , Cytomegalovirus, Epstein-Barr virus and Haemophilus influenzae 2-5 , but some flaviviruses with a documented circulation in Brazil were identified as triggers of GBS in the last two decades, especially dengue virus (DENV), West Nile virus (WNV) and Saint Louis encephalitis virus (SLEV) 4,6-9 .…”
mentioning
confidence: 99%